Investigation of Cortical Glutamate–Glutamine and γ-Aminobutyric Acid in Obsessive–Compulsive Disorder by Proton Magnetic Resonance Spectroscopy - Simpson, Helen B; Shungu, Dikoma C; Bender, James; Mao, Xiangling; Xu, Xiaoyan; Slifstein, Mark; Kegeles, Lawrence S (Neuropsychopharmacology (New York, N.Y.), 2012)
Glutamatergic abnormalities in corticostriatal brain circuits are thought to underlie obsessive-compulsive disorder (OCD). Whether these abnormalities exist in adults with OCD is not clear. We used proton magnetic resonance spectroscopy (¹H MRS) to test our hypothesis that unmedicated adults with OCD have reduced glutamate plus glutamine (Glx) levels in the medial prefrontal cortex (MPFC) compared with healthy controls. Levels of γ-aminobutyric acid (GABA) were also explored. Twenty-four unmedicated adults with OCD and 22 matched healthy control subjects underwent ¹H MRS scans at 3.0 T. Resonances of both Glx and GABA were obtained using the standard J-editing technique and assessed as ratios relative to voxel tissue water (W) in the MPFC (the region of interest) and the dorsolateral prefrontal cortex (DLPFC) to explore the regional specificity of any finding. In the MPFC, Glx/W did not differ by diagnostic group (p=0.98) or sex (p=0.57). However, GABA/W was decreased in OCD (2.16±0.46 × 10⁻³) compared with healthy controls (2.43±0.45 × 10⁻³, p=0.045); moreover, age of OCD onset was inversely correlated with MPFC GABA/W (r=-0.50, p=0.015). MPFC GABA/W was higher in females than in males. In the DLPFC, there were no main effects of diagnosis or gender on Glx/W or GABA/W. These data indicate that unmedicated adults with OCD do not have Glx abnormalities in a MPFC voxel that includes the pregenual anterior cingulate cortex. However, they may have decreased MPFC GABA levels. How GABA abnormalities might contribute to corticostriatal dysfunction in OCD deserves further study.